Mary’s epistemic gain in the knowledge argument - Özdemir, Eyyüphan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
Frank Jackson’s Knowledge Argument claims that a person who knows everything physical about color vision cannot yet know what it is like to see red and this demonstrates that physicalism is false. My thesis largely aims to defend the Acquaintance Hypothesis according to which Mary after seeing colored objects gains non-propositional and non-ability knowledge namely acquaintance knowledge. In addition to this defence, the thesis aims to present the notion of acquaintance knowledge in neural terms thereby making this notion less slippery. I also want to draw attention to the fact that the Acquaintance Hypothesis is compatible with many physicalist considerations grounding other replies to the knowledge argument. Especially the similarities between the Acquaintance Hypothesis and New Knowledge / Old Fact view are worth considering. I will present these common considerations and maintain that the notion of acquaintance knowledge might play a central role in a possible, unified physicalist reply to the knowledge argument. However, this issue needs further research and more detailed investigations.
Keywords: Knowledge, Theory of.